Improving recognition and management of inpatient delirium in Parkinson’s disease: evidence review and implications for clinical care - Coleman, Colin; Smiley, Adrianne; Rosenfeld, Sheera; Brooks, Anne (Frontiers in Aging Neuroscience, 2025)
Delirium is an acute disturbance of attention, arousal, and cognition that fluctuates in severity and is a common yet under recognized complication in hospitalized patients with Parkinson’s disease. In Parkinson’s disease, symptoms such as rigidity, bradykinesia, hallucinations, and slowed thinking overlap with the clinical features of delirium, which can obscure its onset in hospitalized patients. Variability in diagnostic criteria further complicates accurate recognition and prevalence estimates. This mini review summarizes current evidence on the prevalence, risk factors, and consequences of delirium in Parkinson’s disease (PD) and its associations with mortality and institutionalization. A total of 61 reports published between 1990 and 2025 were included across five domains: delirium diagnosis and prevalence, delirium subtypes, PD-specific delirium rates, risk factors and prevention, and treatment considerations. Foundational evidence reviews and official diagnostic documents (e.g., ICD-10, ICD-11, DSM criteria) were also incorporated as they remain internationally recognized standards for delirium diagnosis. Scholarly studies were appraised using the Joanna Briggs Institute (JBI) Critical Appraisal Checklists, with overall evidence quality judged to be moderate to high, while official diagnostic and guideline documents were considered high-quality based on their authoritative, consensus-driven development. Standardized clinical strategies for hospital management remain limited, but the available evidence supports the use of tailored approaches. We present evidence-based implications for clinical care aligned with the Parkinson’s Foundation Hospital Care Standards to improve recognition, prevention, and treatment. We emphasize the need for critical evaluation, methodological consistency, and acknowledgment of the dynamic care challenges posed by delirium in Parkinson’s disease.